Studi Literatur Profil Farmakokinetik dan Penetrasi Antibiotik ke Jaringan Ulkus Diabetik - Munifah Wahyuddin; Dwi Wahyuni Leboe; Khaerani Khaerani; Nurshalati Tahar; Alifia Putri Febriyanti; Nursyamsi Dhuha; Yuliani Yuliani (Jurnal Ilmiah Medicamento, 2022)
A diabetic foot ulcer is a complication of diabetes that causes open sores that can develop into an infection. The selection of the right antibiotics is based on the pharmacokinetic profile of antibiotics that can show antibiotic activity as bactericidal or bacteriostatic, the main bacteria found in diabetic ulcer disease are gram-positive bacteria such as Methicillin-Resistant Staphylococcus aureus (MRSa). This study aims to determine the antibiotics acting on diabetic ulcer tissue and the pharmacokinetic profile and penetration of antibiotics into diabetic ulcer tissue based on a literature study using the PICO (patient/population, intervention, comparison, and outcomes) method. The results of the analysis of 8 articles that met the inclusion criteria showed that the pharmacokinetic profile (PK) of several antibiotics obtained showed bactericidal activity in the treatment of diabetic ulcers including the antibiotics ceftolozane/tazobactam, tedizolid, cefepime, daptomycin, trimethoprim/sulfamethoxazole. Several antibiotics have shown activity as bacteriostatic in the treatment of diabetic ulcers, including linezolid antibiotics and vancomycin antibiotics.